2015
DOI: 10.1590/1415-52732015000300001
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and associated factors in a Portuguese older adult community

Abstract: A B S T R A C T ObjectiveTo evaluate the prevalence of undernutrition in older adults aged ≥75 years living in communities and to identify the main factors independently associated with undernutrition. MethodsA cross-sectional study was conducted using a random sample of family physicians' medical records of 86 older adults aged ≥75 years living in the community studied. Their nutritional status was evaluated using the Mini Nutritional Assessment. ResultsA total of 10.5% of the elderly were undernourished and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
3
14
1
1
Order By: Relevance
“…However, age was not associated to a higher risk of undernutrition in the present study. On the other hand, similar results were found for self‐perception of health status, which are also in line with previous data in a small sample of Portuguese older adults . In addition, in agreement with previous data, undernutrition or undernutrition risk was directly associated with low physical activity, which is expected because mobility is evaluated during undernutrition assessment.…”
Section: Discussionsupporting
confidence: 92%
“…However, age was not associated to a higher risk of undernutrition in the present study. On the other hand, similar results were found for self‐perception of health status, which are also in line with previous data in a small sample of Portuguese older adults . In addition, in agreement with previous data, undernutrition or undernutrition risk was directly associated with low physical activity, which is expected because mobility is evaluated during undernutrition assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies conducted in South Africa, Portugal, and Korea using MNA as the measurement tool, reported prevalence of malnutrition among community-dwelling older persons as 10.4%, 5.6% and 10.5% respectively [5, 20, 48]. In comparison to these studies, the present study found a higher prevalence of malnutrition.…”
Section: Discussioncontrasting
confidence: 66%
“…This positive association between currently married people and overweight is consistent with findings in previous studies [32,33]. We did not find any significant association between marital status and underweight in the adjusted analysis as found in one previous study conducted in elderly people in Portuguese [34]. Urban residence decreased risk of being underweight and overweight compared to rural residence.…”
Section: Discussionsupporting
confidence: 92%